Analysis of Human–Wildlife Conflict in Buffer Villages Surrounding Bogani Nani Wartabone National Park - Regita Cahyani Djibu; Djuna Lamondo; Zuliyanto Zakaria (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Conflict between local communities and wildlife in the buffer villages surrounding Bogani Nani Wartabone National Park (TNBNW) continues to rise due to increasing human pressure on forest ecosystems. This study aims to identify the types of conflict, the wildlife species involved, and community responses to these disturbances. Data were collected through interviews with 30 respondents in East Suwawa and West Dumoga Subdistricts. Results show that most conflicts (90%) are triggered by wildlife perceived as agricultural pests, while 10% are caused by animals entering residential areas. Key species involved include the crested black macaque (Macaca nigrescens), Sulawesi wild boar (Sus celebensis), snakes, lowland anoa (Bubalus depressicornis), and various bird species. Reported disturbances range from crop damage and wildlife presence in farmlands to potential threats to human safety. Most community mitigation efforts are non-lethal, such as installing nets, using spiritus as a repellent, guarding fields with dogs, and setting simple traps. However, hunting still occurs in some areas for crop protection or economic purposes. Habitat loss from encroachment, logging, and land clearing exacerbates conflict by pushing wildlife out of forests into human landscapes. Overall, these findings demonstrate that human–wildlife conflict leads not only to economic losses but also threatens the survival of protected species such as Macaca nigrescens (VU), Sus celebensis (NT), and Bubalus depressicornis (EN). This study demonstrates scientific novelty by presenting an integrated empirical analysis of the forms of human–wildlife conflict, the composition of species involved, and community response patterns in buffer villages surrounding Bogani Nani Wartabone National Park that have not previously been systematically documented, and provides practical contributions by offering an evidence-based foundation for the development of adaptive, non-lethal, and community-based conflict mitigation strategies to support conservation area management and the protection of threatened species.